2022
DOI: 10.4314/dujopas.v7i3b.11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Allium Sativum (Garlic), Zingiber officinale (Ginger) and Syzygium aromaticum (Clove) Extract against Larvae of Aedes mosquitoes (Culicidae: Diptera)

Abstract: Mosquito control has become more difficult due to the unsystematic use of synthetic chemical insecticides which have inauspicious effect on the environment. Botanical phyto-chemicals with mosquitocidal potential are now recognized as potent alternative insecticides to replace synthetic insecticides in mosquito control programs due to their excellent larvacidal activities. The present study assessed the influence of A. sativum (garlic), Z. officinale (ginger) and S. aromatic (clove) extracts against Aedes mosqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Allium sativum (garlic) and Cymbopogon citratus (lemon grass) are plants commonly known and used for their medicinal values in many countries of the world including Nigeria (Odugbemi and Akinsulire, 2006). Previous studies on their phytochemical extracts at different concentrations have shown some insecticidal activities against larvae of mosquito vector species (Ebe et al, 2015;Muhammad et al, 2019;Sitorus et al, 2020;Aminu et al, 2021;Castillo-Morales et al, 2021;). Synergistic combinations of two or more compounds can reduce the adverse effects brought on by high dosages of a single agent, access context-specific multitarget mechanisms, and reduce the chance of resistance development (Lehar et al, 2009;Youssefi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Allium sativum (garlic) and Cymbopogon citratus (lemon grass) are plants commonly known and used for their medicinal values in many countries of the world including Nigeria (Odugbemi and Akinsulire, 2006). Previous studies on their phytochemical extracts at different concentrations have shown some insecticidal activities against larvae of mosquito vector species (Ebe et al, 2015;Muhammad et al, 2019;Sitorus et al, 2020;Aminu et al, 2021;Castillo-Morales et al, 2021;). Synergistic combinations of two or more compounds can reduce the adverse effects brought on by high dosages of a single agent, access context-specific multitarget mechanisms, and reduce the chance of resistance development (Lehar et al, 2009;Youssefi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%